Rush Hour in a National Park—Mobile Encounters in a Peripheral Tourism Landscape - Nousiainen, Minna; Rantala, Outi; Tuulentie, Seija (Springer International Publishing, 2023)
Abstract Remote places are often portrayed as marginal, immobile and static. However, these places are also shaped by various mobility practices which are intertwined in the landscape. In this chapter, we focus on shifting place mobilities through the concept of freedom to roam ( allemansrätten , everyone’s rights) and explore the ways in which it turns into moral aspects of landscape practices and questions of ownership. We approach mobilities from the perspective of relational ontology and investigate how the different types of interconnected local and global mobilities transform into becoming in a landscape. Here, we apply Ingold’s ideas about landscape as a process of temporalities, various movements and mobilities that are continually unfolding and changing. The plurality of ways locals encounter tourism in the landscape of Posio in south-east Lapland, Finland, becomes illustrated through the destinization and commodification of the landscape, changes taking place in the physical landscape and in the embodied ways of using the landscape, as well as in the context of ownership issues related to the landscape. These diverse becomings demonstrate how the seemingly marginalised local mobility practices and local ownership in the landscape are affected by the abruptly increased recreational mobility.